2023
DOI: 10.3390/d15070855
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Gut Microbial Community Structure of Three Tropical Sea Cucumber Species

Abstract: Based on 16S rRNA gene high-throughput sequencing technology, the microbial community structure in the gut of three tropical sea cucumber species, Holothuria atra, Stichopus chloronotus, and S. monotuberculatus, and their habitat sediments were analyzed. The OTUs in the gut contents of S. monotuberculatus, S. chloronotus, H. atra, and their sediments were 2489 ± 447, 1912 ± 235, 1628 ± 150, and 4162 ± 94, respectively. According to alpha diversity analysis (Ace, Chao1, Shannon, Simpson), the richness and diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 82 publications
1
5
1
Order By: Relevance
“…At the phylum level, the bacterial phylum with the highest abundance in demoiselle and common crane samples was Firmicutes. This is consistent with the results for gut bacteria in captive common and demoiselle cranes (Wang, 2022). Research has indicated that Firmicutes are more abundant in herbivorous animals (Wang et al, 2022), and their main function is to break down cellulose into volatile fatty acids that can be assimilated by the host, increase nutrient utilization, regulate T cells to strengthen host immunity, inhibit intestinal inflammation, and maintain the ecological balance of the gut microbiota (Fernando et al, 2010;Guan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At the phylum level, the bacterial phylum with the highest abundance in demoiselle and common crane samples was Firmicutes. This is consistent with the results for gut bacteria in captive common and demoiselle cranes (Wang, 2022). Research has indicated that Firmicutes are more abundant in herbivorous animals (Wang et al, 2022), and their main function is to break down cellulose into volatile fatty acids that can be assimilated by the host, increase nutrient utilization, regulate T cells to strengthen host immunity, inhibit intestinal inflammation, and maintain the ecological balance of the gut microbiota (Fernando et al, 2010;Guan et al, 2017).…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, 16S rRNA and ITS high-throughput sequencing was performed to analyze the diversity and composition of gut bacteria and fungi of common and demoiselle cranes migrating to the Yellow River Wetland. The results suggested that the α-diversity of the gut microbial of demoiselle cranes was remarkably higher than that of common cranes, and this differed from findings presented in another study analyzing the gut microbial diversity of five species of captive cranes (Wang, 2022). Studies have demonstrated that a more diverse food composition results in a higher diversity and richness of the host gut microbiota (Lau et al, 2018).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Whether in the dry season or the wet season, Proteobacteria had the highest abundance in all samples. These bacteria, generally Gram-negative, are widely distributed and diverse in shape, which are the dominant phylum identified in the gut contents of numerous marine invertebrates [26][27][28][29][30]. The amount of research on gut microbes of A. japonicus is most frequent among Holothuroidea species, and Proteobacteria always occupy the dominant position [10,31,32].…”
Section: Dominant Gut Bacterial Communitymentioning
confidence: 99%
“…We also compared the results of current research with previous studies that focused on the dominant gut bacterial community of the same sea cucumber species in the wild environment. Plotieau et al (2013) collected H. scabra from the intertidal zone at different seasons to explore the bacterial diversity of sediments transiting through the gut of these species, and Wang et al (2023) analyzed the gut microbial community structure of S. monotuberculatus with other two sea cucumber species in the wet season [30,39]. The results showed that, at the phylum level, Proteobacteria was still the dominant gut bacterial community even in a natural environment.…”
Section: Dominant Gut Bacterial Communitymentioning
confidence: 99%